Pax Democratica - Huntley, James Robert. author. aut Link
XVIII, 243 p. 10 illus.
Keywords: After a turbulent century characterized by vast bloodshed, but also by the spread of democratic government and humane values, the author suggests that the great democracies - led by Britain, France, Germany, Japan and the United States - should form an intercontinental community of democracies - a Pax Democratica according to the author. He argues that such a union will culminate centuries of evolution in world order: from empires to balance-of-power Realpolitik , more recently from cooperative international institutions to an era of supranational communities, composed of likeminded peoples and organized around democratic principles.